Decolonizing marketing. Issue 2 (4th March 2022) - Eckhardt, Giana M.; Belk, Russell; Bradford, Tonya Williams; Dobscha, Susan; Ger, Güliz; Varman, Rohit
ABSTRACT: In January 2021, the ETHOS Research Center at Bayes Business School, along with the CRIS Research Center at Royal Holloway University of London, hosted an event entitled Decolonizing the Business School. Over 500 attendees participated, from all business disciplines, testifying to the strong levels of interest in this topic. Marketing was particularly active, with over 100 participants. In this article, I (Giana Eckhardt, one of the organizers of the event) speak with the marketing break out room facilitators – Russ Belk, Tonya Bradford, Susan Dobscha, Güliz Ger and Rohit Varman – in a wide-ranging conversation about what decolonization means to the field of marketing, and what marketing academics can do if they would like to explore these ideas further. First, we offer a brief introduction to decolonization. Also, a list of resources for the interested reader is presented as well as ideas for further exploration in this nascent domain at the end.